Efficient 2-phosphoglycolate degradation is required to maintain carbon assimilation and allocation in the C4 plant Flaveria bidentis. (23rd October 2018) - Levey, Myles; Timm, Stefan; Mettler-Altmann, Tabea; Luca Borghi, Gian; Koczor, Maria; Arrivault, Stéphanie; PM Weber, Andreas; Bauwe, Hermann; Gowik, Udo; Westhoff, Peter
Abstract : Photorespiration is essential for maintaining high rates of C4 photosynthesis by preventing the 2-phosphoglycolate-mediated inhibition of carbon utilization efficiency. Abstract: Photorespiration is indispensable for oxygenic photosynthesis since it detoxifies and recycles 2-phosphoglycolate (2PG), which is the primary oxygenation product of Rubisco. However, C4 plant species typically display very low rates of photorespiration due to their efficient biochemical carbon-concentrating mechanism. Thus, the broader relevance of photorespiration in these organisms remains unclear. In this study, we assessed the importance of a functional photorespiratory pathway in the C4 plant Flaveria bidentis using knockdown of the first enzymatic step, namely 2PG phosphatase (PGLP). The isolated RNAi lines showed strongly reduced amounts of PGLP protein, but distinct signs of the photorespiratory phenotype only emerged below 5% residual PGLP protein. Lines with this characteristic were stunted in growth, had strongly increased 2PG content, exhibited accelerated leaf senescence, and accumulated high amounts of branched-chain and aromatic amino acids, which are both characteristics of incipient carbon starvation. Oxygen-dependent gas-exchange measurements consistently suggested the cumulative impairment of ribulose-1, 5-bisphosphate regeneration with increased photorespiratory pressure. Our results indicate that photorespiration is essential for maintaining high rates of C4 photosynthesis by preventing the 2PG-mediated inhibition of carbon utilization efficiency. However, considerably higher 2PG accumulation can be tolerated compared to equivalent lines of C3 plants due to the differential distribution of specific enzymatic steps between the mesophyll and bundle sheath cells.